Didáctica de Lenguas Extranjeras - TR421 - 202301 - Universidad Peruana de Ciencias Aplicadas (UPC) (2023)
Didáctica de Lenguas Extranjeras is an elective course in the curriculum program for translators and interpreters. It is the second course in the track of courses for Didáctica de Lenguas Extranjeras minor. The course will address class activities and online tasks to describe, analyze, and propose teaching strategies in the field of second language acquisition. Translation and Interpreting students will have the opportunity to consolidate their English language skills and complement their studies by reflecting on the process of second language teaching and learning.